H HUBUNGAN FILSAFAT DENGAN ILMU PENDIDIKAN: AKAR FILOSOFIS DALAM PRAKTIK PENDIDIKAN AGAMA ISLAM MATERI QURAN HADITS - Mutia Dewi; M Sirozi; Abdurrahmansyah; Sri Safrina (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to examine the relationship between philosophy and educational science as the philosophical roots of Islamic religious education practices, particularly in the context of the Quran and Hadith. This study highlights the importance of understanding philosophical values ​​in improving the quality of learning and instilling profound spiritual and ethical meaning in students. The methods used were literature study and conceptual analysis to explore the philosophical foundations relevant to the practice of Islamic religious education. The results of the study indicate that the integration of philosophical principles into educational science can enrich teaching methods, so that learning the Quran and Hadith is not merely rote, but also fosters authentic character and understanding, as well as moral responsibility